Brain gliomas new transcriptomic discoveries from differentially expressed genes to therapeutic targets - Shiwen Pei; Zhiquan Jiang; Hongwei Cheng (Scientific Reports)
Abstract Gliomas are a prevalent form of primary malignant brain tumor, yet the intricate molecular mechanisms underlying its pathogenesis remain unclear. This study aimed to identify new genetic targets linked to glioma by analyzing microarray datasets to uncover genetic factors involved in its onset and progression. We obtained two independent glioma datasets from the Gene Expression Omnibus database, processed and normalized them using R software, and evaluated the relationship between differentially expressed genes and glioma by differential expression, expression quantitative trait loci, and Mendelian randomization (MR) analyses. Gene set enrichment analysis and immunocytometric analysis further explored the biological functions and pathways of identified genes, which were validated using The Cancer Genome Atlas and Genotype-Tissue Expression datasets. We identified eight co-expressed genes—C1QB, GPX3, LRRC8B, TRIOBP, SNAPC5, SPI1, TSPYL5, and FBXL16—that are crucial in various biological processes. CIBERSORT analysis revealed significant immune cell-type distributions within gliomas, underscoring the significance of immune cell infiltration. Validation in additional datasets confirmed the MR analysis results and upstream regulatory factors were identified using NetworkAnalyst. Our findings offer fresh perspectives on the molecular underpinnings of glioma and highlight potential targets for therapeutic interventions.